2017
DOI: 10.4103/jnrp.jnrp_472_16
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive versus Open Spine Surgery: What Does the Best Evidence Tell Us?

Abstract: Background:Spine surgery has been transformed significantly by the growth of minimally invasive surgery (MIS) procedures. Easily marketable to patients as less invasive with smaller incisions, MIS is often perceived as superior to traditional open spine surgery. The highest quality evidence comparing MIS with open spine surgery was examined.Methods:A systematic review of randomized controlled trials (RCTs) involving MIS versus open spine surgery was performed using the Entrez gateway of the PubMed database for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…We 5,6 However, they found no significant difference in pain improvement between the two groups. 1 We have the same result as per hospital stay, however our study demonstrated better pain relief in open surgery group.…”
Section: Resultsmentioning
confidence: 73%
“…We 5,6 However, they found no significant difference in pain improvement between the two groups. 1 We have the same result as per hospital stay, however our study demonstrated better pain relief in open surgery group.…”
Section: Resultsmentioning
confidence: 73%
“…Early on, Harrington's eponymous rods were also patient-specific and used in select cases prior to the transition to larger patient groups, widespread use and acceptance [41]. On the other hand, spinal surgeons and pioneers must not allow a sound theoretical basis, successful application in other fields and encouraging early results to drive unsubstantiated, widespread application, as some argue has occurred with certain Minimally Invasive Spinal Surgeries (MISS) [42]. Further, the possibility of unforeseen implant-related complications must not be discounted, either due to issues in the planning and implementation of a PSI [6] or inherent to the implant design or material [11,18,43].…”
Section: Discussionmentioning
confidence: 99%
“…Although PELD and MIS-TLIF are increasingly popular, minimally invasive surgery also brings no-negligible radiation exposure to surgeons, especially in lumbar spine surgery [ 36 ]. It is still unclear whether this exposure is harmful to patients, and this problem needs to be solved.…”
Section: Discussionmentioning
confidence: 99%